Land girls. Series 1 [videorecording (DVD)] - Hughes, Steve; Hossington, Erika; Parker, Nathaniel, 1962-; Ward, Sophie; Strallen, Summer; Gemmell, Becci; Woodcock, Jo, 1988-; Boyle, Liam, 1985-; Benton, Mark, 1965- (BFS Video, 2010)
Set in England during the Second World War, a five-part drama that captures the sacrifices and experiences of four young women in the Women's Land Army. Sharing hardships and working alongside captured POWs, Annie, Bea, Joyce and Nancy toil in the fields to grow food for the war effort.